Caracterização de biominerais a partir das interações entre vivianita e acidithiobacillus ferrooxidans, sob diferentes substratos sedimentares, como potencial para bioassinaturas em condições marcianas pretérita - Janolla, Thaís de Agrella (2023)
The concept of “life” has not yet been established, nor has its origin been clarified. This represents a challenge for the areas of science that strive to investigate the possibility of life in environments other than Earth. Thus, NASA, in a transdisciplinary effort, has increasingly promoted space technologies with the aim of investigating places suitable for the establishment of life on Mars and identifying their biosignatures. Therefore, studying and characterizing biominerals and chemiofossils on our planet is extremely important, considering the fundamental processes that lead to the synthesis of minerals in the presence of microorganisms. This will provide a knowledge base that will enable comparisons with rocks and sediments from Mars. In vitro experimental approaches become important due to the possibility of a detailed study of these processes in controlled environments. Thus, the oxidation of Vivianite, iron phosphate common on Earth and potentially present on Mars, by the bacteria Acidithiobacillus ferrooxidans was studied to obtain energy, with the aim of characterizing the precipitates formed when different substrates are present. To this end, characterization techniques such as micro-Raman FT-IR and SEM-EDS were applied. Therefore, we contributed to the understanding of the formation of biosignatures and the influence of substrates, and can be applied to terrestrial and Martian environments.